Upaya Pengoptimalan Laba dengan Metode Pencatatan dan Metode Penilaian Persediaan - Ria Ayu Trianingsih; Muhammad Hasyim Ashari (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2023)
The purpose of this research is to choose a method of recording and valuing inventory of finished goods that can increase profits at CV Istana Boneka Malang. The research approach used in this study is a quantitative approach. The analysis technique used is to use a comparison between perpetual and periodic inventory recording methods to determine the cost of goods sold and gross profit earned by the company. The results showed that the selection of the method of recording and valuation at CV Istana Boneka Malang that should be used is the inventory recording method using the LIFO inventory valuation method, where this method provides a higher gross profit than other valuation methods. However, as stated in Article 10 paragraph (6) of Law Number 36 of 2008 concerning Income Tax which states that the method that is fiscally permissible is the Average or FIFO inventory valuation method, CV Istana Boneka Malang can use the inventory recording method with the inventory valuation method. Average as a consideration of the method produces the highest gross profit after the LIFO inventory valuation method.